2005
DOI: 10.1007/s10441-005-4880-5
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Model of the Self-Sustained Oscillating Contractions of Cardiac Myocytes

Abstract: Computational cell models appear as necessary tools for handling the complexity of intracellular cell dynamics, especially calcium dynamics. However, while oscillating intracellular calcium oscillations are well documented and modelled, a simple enough virtual cell taking into account the mechano-chemical coupling between calcium oscillations and cell mechanical properties is still lacking. Considering the spontaneous periodic contraction of isolated cardiac myocytes, we propose here a virtual cardiac cell mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…While measurement of fiber strains in the left ventricle are in agreement with longitudinal strains measured in isolated cardiomyocytes [33,51], strain measurements along cross-fiber directions in left ventricular wall indicate that cross-fiber shortening is greater than longitudinal fiber shortening, except for the epicardial region [36,22]. We explain this macroscopic behavior through a simple geometrical model that links the microscopic deformation with the macroscopic one.…”
Section: Linking Micro To Macrosupporting
confidence: 48%
“…While measurement of fiber strains in the left ventricle are in agreement with longitudinal strains measured in isolated cardiomyocytes [33,51], strain measurements along cross-fiber directions in left ventricular wall indicate that cross-fiber shortening is greater than longitudinal fiber shortening, except for the epicardial region [36,22]. We explain this macroscopic behavior through a simple geometrical model that links the microscopic deformation with the macroscopic one.…”
Section: Linking Micro To Macrosupporting
confidence: 48%
“…Such perturbations correspond to the experimentally observed calcium sparks attributed to the local and concerted opening of a small number of ryanodine receptors (Sheehan et al 2006;Cheng & Lederer 2008). Kinetic parameter values used in the simulations (table 1) have been taken in the range of values reported by Dupont & Goldbeter (1992 and chosen in order to get cell contraction features that correspond to the measurements extracted from time-lapse videomicroscopy experiments (Pustoc'h et al 2005). Typically, contraction periodicity is approximately 10-18 s, with a contraction/relaxation phase lasting approximately 0.9-1.5 s and producing a typical cell shortening of 4-10% of cell length.…”
Section: (B) Finite-element Simulations Of Different Rhythmic Contracmentioning
confidence: 76%
“…Let us notice that these values are significantly larger than the ones considered by Qin et al (2007), and this point will be addressed in the discussion section. Preliminary simulation results (Pustoc'h et al, 2005) have shown that PAGs may experience large deformations during cardiomyocyte contraction. Thus, we modelled PAGs as nearly incompressible neo-Hookean medium defined by a strain energy function W pag .…”
Section: Modelling Pags Mechanical Propertiesmentioning
confidence: 98%
“…We previously derived from uniaxial traction experiments on isolated cardiomyocyte (Cazorla et al, 2003) a Young's modulus value E cell $6a cell $30 kPa (Pustoc'h et al, 2005), which fits quite well with the value of 35.1 kPa reported for the apparent elastic modulus of rat cardiomyocytes probed by atomic force microscopy indentation (Lieber et al, 2004). Considering again the explicit relationship between Young's modulus E cell of the cardiomyocyte and the material constant a cell for small extension ratio (Section 2), we used in our simulations the value a cell ¼ 5 kPaU…”
Section: Characterization Of Cardiomyocyte Elasticity By a Strain Enementioning
confidence: 99%
See 1 more Smart Citation